Rokeya and woolf: souls that have lived - Hasan, Md. Mahmudul (Mahfuz Anam, 2018)
There are some amazing similarities between the Bengali writer Rokeya Sakhawat Hossain (1880-1932) and her English counterpart Virginia Woolf (1882-1941) that will make you wonder whether every great soul that has ever lived experiences the same dimension of reality in different shapes. Both wrote in the early twentieth century and are authors of fiction and non-fiction works. Both were born into two rich, illustrious families and had learned fathers. Rokeya's father Zahiruddin Muhammad Abu Ali Hyder Saber was a well-versed individual in a number of languages and was given the title of a zamindar by the colonial government. Woolf's father Leslie Stephen was a prominent Victorian editor and biographer and was knighted in 1901 by the British monarch.